2021
DOI: 10.1136/bmjopen-2020-046658
|View full text |Cite
|
Sign up to set email alerts
|

Do people with mental health problems have lower adherence to precautionary measures in COVID-19 pandemic? A cross-sectional observational study in Hong Kong

Abstract: ObjectivesMental health problems are prevalent during the COVID-19 pandemic, but their effect on adherence to precautionary measures is not well understood. Given that psychological morbidities are associated with lower treatment adherence, and that precautionary measures are important in containing the spread of COVID-19, this study aims to determine if people with mental health problems have lower adherence to precautionary measures against COVID-19.DesignWe conducted a cross-sectional territory-wide online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
9
2
Order By: Relevance
“…It is possible that in the Taiwan study conducted in February 2020, at the beginning of the epidemic general anxiety levels were higher (48.8%) leading to higher adherence behaviour [ 15 ], while in our study later in the epidemic (December 2020-February 2021) general anxiety levels were lower (21.7%) associated with lower adherence behaviour. Unlike some previous research that showed that having depressive symptoms decreased adherence to COVID-19 preventive measures [ 17 ], and having psychological distress (anxiety, depression) increased adherence to COVID-19 preventive measures [ 20 ], we did not find any significant association between depressive symptoms and any specific and summative COVID-19 preventive behaviour. In high-income countries most studies show a positive association between anxiety and adherence to COVID-19 preventive measures, while depressive symptoms had negative or positive associations with adherence to COVID-19 preventive measures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is possible that in the Taiwan study conducted in February 2020, at the beginning of the epidemic general anxiety levels were higher (48.8%) leading to higher adherence behaviour [ 15 ], while in our study later in the epidemic (December 2020-February 2021) general anxiety levels were lower (21.7%) associated with lower adherence behaviour. Unlike some previous research that showed that having depressive symptoms decreased adherence to COVID-19 preventive measures [ 17 ], and having psychological distress (anxiety, depression) increased adherence to COVID-19 preventive measures [ 20 ], we did not find any significant association between depressive symptoms and any specific and summative COVID-19 preventive behaviour. In high-income countries most studies show a positive association between anxiety and adherence to COVID-19 preventive measures, while depressive symptoms had negative or positive associations with adherence to COVID-19 preventive measures.…”
Section: Discussioncontrasting
confidence: 99%
“…In a large online survey among the general adult population in Germany early 2020, general anxiety symptoms were positively associated with adherence to COVID-19 safety behaviours [ 18 ]. During the severe acute respiratory syndrome (SARS) in 2003 in Hong Kong, among the general adult population higher anxiety levels were associated with higher uptake of protective measures [ 19 ], and in an online survey in June/July 2020 in Hong Kong, people with psychological distress were more likely to adhere to COVID-19 preventive measures [ 20 ]. Based on few previous studies in high-income countries, it can be hypothesized that psychological distress (anxiety, depression) influences adherence to COVID-19 preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…This study was a secondary analysis of a cross-sectional survey conducted in Hong Kong during the COVID-19 pandemic ( 46 ). This planned secondary analysis specifically concerned age differences and prevalence of mental health problems of the same cohort.…”
Section: Methodsmentioning
confidence: 99%
“…As this was a secondary analysis of an earlier published study, the sample size was predetermined ( 46 ). Statistical analysis was performed using the IBM SPSS Statistics, Version-26.0 (IBM Corp).…”
Section: Methodsmentioning
confidence: 99%
“…Also, concerns about the risk of death from COVID-19, misinformation, disinformation, poor access to vaccination and health care in addition to stigma and discrimination associated with COVID-19 [30] exacerbated the risk of COVID-19 related mental problems. The prevalence of depression is as high as 30% in sub-Saharan Africa [31] Prior studies suggest that people with depression and mental challenges complied better with preventive measures [32,33]. Another study however, reported that depression was associated with lower compliance with COVID-19 precautionary measures [34].…”
Section: Introductionmentioning
confidence: 99%